Prosze jak najszybciej ; ))
I najlepiej z obliczeniami ; ]]

Doprowadź do najprostszej postaci
a) 2(3a-4b+c)-5(3a+b-2c)=
b) 7(x+2y-3z)+4(2x-3y-5z)=
c) -3(-2a-4b-c)-6(a-2b-6c)=
d) -5(2x-2y-6z)-(x-7y-3z)=
e) 2(a-3b)-3(a-b)-5(4a+3b)=
f) -3(2x-3y)+5(x+2y)-2(3y-x)=
g) 5(b-2a)+3(a-3b)-4(2a-4b)=
h) -7(2a+3b)-9(a-2b)-3(3a+4b)=
i) (x²-6x+18):3+(x²-3x+5):2=
j) (x³-6x²+8x):(-2x)+(12-9x-3x²)=
k) (x²-5x+15):(-5)+(7-2x+3x²):2=
l) (8-10x+4²)+(12x³-21x²-6x):(-3x)=
ł) 4(x³-2x²-5x+2)-x(2x²-3x+5)=
m) 2x(x²-3x+7)+3(x³-2x²+4)=
n) -3x(-2x²-4x+1)-5(x³-3x+2)=
o) -3(x³+4x-2)+2x(x²-3x)=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T23:53:22+01:00
Doprowadź do najprostszej postaci
a) 2(3a-4b+c)-5(3a+b-2c)=6a-8b+2c-15a-5b+10c=-9a-13b+10c
b) 7(x+2y-3z)+4(2x-3y-5z)=7x+14y-21z+8x-12y-20z=15x+2y-41z
c) -3(-2a-4b-c)-6(a-2b-6c)=6a+12b+3c-6a+12b+36c=24b+39c
d) -5(2x-2y-6z)-(x-7y-3z)=-10x+10y+30z-x+7y+3z=-11x+17y+33z
e) 2(a-3b)-3(a-b)-5(4a+3b)=2a-6b-3a+3b-20a-14b=-21a-17b
f) -3(2x-3y)+5(x+2y)-2(3y-x)=-6x+9y+5x+10y-6y+2x=x+13y
g) 5(b-2a)+3(a-3b)-4(2a-4b)=5b-10a+3a-9b-8a+16b=14b-15b
h) -7(2a+3b)-9(a-2b)-3(3a+4b)=-14a-21b-9a+18b-9a-12b=-32a-15b
i) (x²-6x+18):3+(x²-3x+5):2 /*6=2(x²-6x+18)+3(x²-3x+5)=2x²-12x+36+3x²-9x+15=5x²-21x+51
j) (x³-6x²+8x):(-2x)+(12-9x-3x²)=(x²-6x+8):(-2)+(12-9x-3x²) /*(-2)=-2x²+12x-16-24+18x+6x²=4x²+30x-40
k) (x²-5x+15):(-5)+(7-2x+3x²):2 /*10=-2x²+10x-30+35-10x+15x²=13x²+5
l) (8-10x+4²)+(12x³-21x²-6x):(-3x)=8-10x+16-4x²+7x+2=-4x²-3x+26
ł) 4(x³-2x²-5x+2)-x(2x²-3x+5)= 4x³-8x²-20x+8-2x³+3x²-5x=2x³-5x²-25x+8
m) 2x(x²-3x+7)+3(x³-2x²+4)=2x³-6x²+14x+3x³-6x²+12=5x³-12x²+14x+12
n) -3x(-2x²-4x+1)-5(x³-3x+2)=6x³+12x²-3x-5x³+15x-10=x³+12x²-12x-10
o) -3(x³+4x-2)+2x(x²-3x)=-3x³-12x+2x³-6x²=-x³-6x²-12x
2010-03-01T00:02:38+01:00
A) 2(3a-4b+c)-5(3a+b-2c)=
6a-8b+2c-15a-5b+10c=
-9a-13b+12c

b) 7(x+2y-3z)+4(2x-3y-5z)=
7x+14y-21z+8x-12y-20z=
15x+2y-41z

c) -3(-2a-4b-c)-6(a-2b-6c)=
6a+12b+3c-6a+12b+36c=
24b+39c

d) -5(2x-2y-6z)-(x-7y-3z)=
-10x+10y+30z-x+7y+3z=
-11x+17y+33z

e) 2(a-3b)-3(a-b)-5(4a+3b)=
2a-6b-3a+3b-20a-15b=
-21a-18b

f) -3(2x-3y)+5(x+2y)-2(3y-x)=
g) 5(b-2a)+3(a-3b)-4(2a-4b)=
h) -7(2a+3b)-9(a-2b)-3(3a+4b)=
i) (x²-6x+18):3+(x²-3x+5):2=
j) (x³-6x²+8x):(-2x)+(12-9x-3x²)=
k) (x²-5x+15):(-5)+(7-2x+3x²):2=
l) (8-10x+4²)+(12x³-21x²-6x):(-3x)=
ł) 4(x³-2x²-5x+2)-x(2x²-3x+5)=
m) 2x(x²-3x+7)+3(x³-2x²+4)=

n) -3x(-2x²-4x+1)-5(x³-3x+2)=
6x³+12x²-3x-5x³+15x-10=
-x³+12x²+12x-10

o) -3(x³+4x-2)+2x(x²-3x)=
-3x³-12x+6+2x³-6x²=
-x³-6x²-12x+6

reszte zrobie jutro